Composite material of metal antimony and carbon as well as preparation method and application of composite material

Through uniform mixing of liquid carbon source ethylene glycol and antimony trichloride in the solvent-thermal reaction, and in-situ carbon coating is achieved using hydrothermal carbon spheres, the problem of poor effect of carbon-coated antimony composite materials prepared by solid carbon sources is solved, and the circulation stability and electrochemical properties of the material are significantly improved.

CN119786545APending Publication Date: 2025-04-08TECH TRAINING CENT OF STATE GRID HUBEI ELECTRIC POWER CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311538504.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-17
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The carbon-coated antimony composite materials prepared by existing solid carbon sources have poor effect and poor material circulation performance, resulting in limited application of antimony in sodium ion batteries.

Method used

The liquid carbon source ethylene glycol and antimony trichloride are used to mix uniformly in the solvothermal reaction, and the hydrothermal carbon spheres are used as catalysts and nucleation agents to achieve in situ carbon coating, and the reaction conditions are regulated to increase the carbon content.

Benefits of technology

The uniform coating of metal antimony and carbon composite materials is achieved, which significantly improves the cyclic stability and electrochemical performance of the material. Especially in the negative electrode application of sodium ion battery, the capacity retention rate reaches 104%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786545A_ABST
    Figure CN119786545A_ABST
Patent Text Reader

Abstract

The invention discloses a metal antimony and carbon composite material, a preparation method and application thereof, and the preparation method comprises the following steps: dissolving antimony trichloride in ethylene glycol, then adding hydrothermal carbon spheres, uniformly stirring, then transferring to a reaction kettle for solvothermal reaction, heating to a set temperature and holding time to obtain a precursor, and drying to obtain the metal antimony and carbon composite material. And finally, reducing the precursor into the metal antimony and carbon composite material in a high-temperature reducing atmosphere. The liquid ethylene glycol is used as a carbon source, the hydrothermal carbon spheres are used as a catalyst, in-situ polymerization of ethylene glycol can be remarkably promoted, a precursor is coated with a polymer, the antimony and carbon composite material with a good coating effect can be obtained after pyrolysis, the used raw materials are low in cost, the synthesis method is simple, the carbon and antimony components of the obtained composite material are controllable, and the preparation method is simple. Wherein the carbon content is between 15.2 wt% and 68.4 wt%, and when the composite material is used as a negative electrode material of an alkali metal ion battery, the problem of poor cycle performance of the material can be solved, and the composite material has outstanding electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of alkali metal batteries, and specifically relates to a composite material of metal antimony and carbon, a preparation method and application thereof. The prepared composite material of metal antimony and carbon can be particularly used in the field of alkali metal batteries. Background Art

[0002] In recent years, sodium-ion batteries have become a new energy storage technology that has attracted much attention due to their abundant resources and low cost. Hard carbon is the most widely studied negative electrode material for sodium-ion batteries. However, its relatively low reaction potential (≈0V vs. + / Na), lower capacity (<350mAh g -1 ) and poor rate performance, which limits its application under fast charge and discharge conditions. Compared with hard carbon negative electrode materials, metal negative electrode materials with alloy mechanisms have higher capacity and slightly higher reaction potential than hard carbon. These characteristics make them very suitable as negative electrode materials for sodium ion batteries. Among them, metal antimony (Sb) has a high theoretical capacity (660mAh g -1 ) and the appropriate potential (0.6 V vs Na / Na + However, Sb has a 390% volume change during the reaction with Na, which causes the active material to fall off the current collector and causes rapid capacity decay. These problems are the biggest obstacles to its practical application.

[0003] At present, the cycling stability of Sb can be improved by designing favorable nanostructures and alloying. In general, the nanostructure of Sb can relieve stress by providing expansion space, while the alloy of Sb can reduce the reversible capacity and thus the volume expansion by adding inert components to Sb; however, the relatively high cost of these methods limits their application. Compared with the strategies of nano-sizing and alloying, carbon coating is considered to be a more economical and easier to operate method. In order to achieve a good Sb coating effect, in-situ and uniform carbon coating is most important for electrode materials. However, due to the uneven mixing of carbon source and Sb precursor and the lack of organic Sb precursor, the coating effect of the carbon layer in the composite material coated with Sb by solid carbon source is poor. For example, the carbon-coated Sb prepared by high-energy ball milling shows the problem of uneven carbon shell thickness; on the other hand, the carbon-coated Sb composite material prepared by pyrolysis of Sb oxide mixed with carbon source often shows the disadvantage of low interface strength between Sb and carbon. These problems lead to rapid capacity decay of Sb composites during cycling. For example, the capacity of graphene-coated Sb nanoparticles rapidly decreases from 250 mAh g to 400 mAh g after 30 cycles. -1 Down to 150mAhg -1 .

[0004] Based on the above-mentioned problems that the carbon-coated Sb prepared by solid carbon source has poor effect and poor material cycle performance, the present invention proposes a composite material for preparing carbon in situ coated Sb using liquid carbon source, which is used for negative electrode materials of sodium ion batteries. In this composite material, Sb can be evenly mixed with the carbon source at the molecular level, and the carbon source can be polymerized in situ on the surface of Sb to achieve a good coating effect; moreover, by additives (such as hydrothermal carbon balls) and reaction conditions (reaction time and temperature), the coated carbon content can be significantly regulated and the coating effect can be improved. The carbon-coated Sb prepared by this technology is used for negative electrode materials of sodium ion batteries, with a simple preparation process, low cost, and good cycle stability. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a metal antimony and carbon composite material to solve the problems of poor carbon-coated Sb effect and poor material cycle performance in the existing solid carbon source preparation.

[0006] Another object of the present invention is to provide a composite material of metal antimony and carbon prepared by the above method.

[0007] Another object of the present invention is to provide an application of a composite material of metal antimony and carbon.

[0008] To achieve the above object, the present invention adopts the following technical solution:

[0009] A method for preparing a metal antimony and carbon composite material comprises the following steps: dissolving antimony trichloride in ethylene glycol, then adding hydrothermal carbon balls as a catalyst, stirring evenly, transferring the mixture to a reaction kettle for solvent thermal reaction, heating the mixture to a set temperature and insulation time to obtain a precursor, and finally reducing the precursor to the metal antimony and carbon composite material in a high-temperature reducing atmosphere.

[0010] As a further preferred embodiment of the present invention, the mass fraction of carbon in the prepared composite material of metal antimony and carbon ranges from 15.2wt% to 68.4wt%.

[0011] As a further preferred embodiment of the present invention, the mass ratio of the hydrothermal carbon balls to antimony trichloride is 1:100, and the amount of ethylene glycol added is 70-80% of the volume of the reactor.

[0012] As a further preferred embodiment of the present invention, the hydrothermal carbon spheres are prepared by a glucose hydrothermal method.

[0013] As a further preferred embodiment of the present invention, the temperature of the solvent thermal reaction is 180-200°C.

[0014] As a further preferred embodiment of the present invention, the solvent thermal reaction time is 24-48 hours.

[0015] As a further preferred embodiment of the present invention, the high-temperature reduction temperature of the precursor is 500-700°C.

[0016] According to another aspect of the present invention, the present invention also provides a composite material of metal antimony and carbon, which is prepared by the above method.

[0017] In addition, the present invention also provides the use of the composite material of metal antimony and carbon as a negative electrode material in an alkali metal ion battery.

[0018] In the preparation process of the present invention, a hydrothermal carbon ball induced solvent thermal synthesis method is adopted, and a precursor of organic matter coated Sb4O5Cl2 is first prepared, and then the precursor of organic matter coated Sb4O5Cl2 is in situ converted into a composite material of carbon wrapped Sb at high temperature. In the solvent thermal reaction process, ethylene glycol not only provides a liquid reaction environment as a reaction reagent, but also ethylene glycol, as a molecular carbon source, can undergo polymerization reaction with SbCl3. In the polymerization reaction, SbCl3 is hydrolyzed into Sb4O5Cl2, wherein the Cl ions in Sb4O5Cl2 can participate in the polymerization reaction, ensuring that the polymer is coated on the Sb4O5Cl2 precursor. The added hydrothermal carbon ball, as a nucleating agent and catalyst, greatly promotes the polymerization process and achieves a better coating effect. At the same time, by adjusting the solvent thermal reaction time, adding hydrothermal carbon balls, and the high temperature reduction temperature of the precursor, the carbon content in the composite material can be significantly increased from 15wt% to 68.4wt%. In addition, the preparation method is simple, economical, and easy to operate. The Sb in the obtained composite material is uniformly dispersed and coated with a carbon layer, which has good interface strength and can effectively solve the problem of poor coating effect. When the composite material is used for the negative electrode of a sodium ion battery (it can also be used for a lithium ion battery or a potassium ion battery), it has a capacity retention rate of 104% after 200 cycles. The material has the advantages of low preparation cost, good coating effect, and excellent electrochemical performance, and is of great significance in promoting sodium ion batteries.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention found that Sb4O5Cl2 precursor is generated after solvothermal reaction in ethylene glycol, and a lot of organic polymers are in situ coated on the surface of Sb4O5Cl2 precursor. The organic polymers are products of ethylene glycol polymerization, where Cl ions in Sb4O5Cl2 play a bridging role with organic matter and participate in the polymerization reaction. After high-temperature reduction, the product after the reaction can be in situ coated on its surface as a carbon source, and the coated carbon content is as high as 15wt%.

[0021] (2) The present invention found that adding only 1wt% of hydrothermal carbon spheres as nucleating agent and catalyst during the solvent thermal reaction can significantly promote the polymerization effect of ethylene glycol and SbCl3, resulting in a high content of organic matter coated on the precursor. No research in this area has been reported so far; moreover, the carbon content of the coating after high-temperature reduction of the precursor is as high as 52.5wt%.

[0022] (3) Compared with the common solid carbon source coating technology, ethylene glycol is a liquid carbon source that can ensure mixing at the molecular level. Moreover, ethylene glycol has a strong polymerization reaction with SbCl3 and hydrothermal carbon balls, ensuring the formation of a uniform coating carbon layer on the Sb surface, making the coating effect more uniform.

[0023] (4) In the carbon-coated Sb composite material prepared by the present invention, the carbon content can be simply achieved by adjusting the reaction time, the amount of hydrothermal carbon balls added, the high-temperature reduction temperature and other factors. For example, when the solvent thermal reaction time is 24h and the high-temperature reduction temperature is 700°C, the carbon content in the composite material is 15wt%; when 1wt% hydrothermal carbon balls are added, the solvent thermal reaction time is 24h, and the high-temperature reduction temperature is 700°C, the carbon content of the composite material is 52.5wt%; when 1wt% hydrothermal carbon balls are added, the solvent thermal reaction time is 24h, and the high-temperature reduction temperature is 600°C, the carbon content of the composite material is 48.5wt%; when 1wt% hydrothermal carbon balls are added, the solvent thermal reaction time is 48h, and the high-temperature reduction temperature is 700°C, the carbon content of the composite material is 68.4wt%.

[0024] (5) The carbon-coated Sb composite material obtained by the present invention has excellent cycle performance when used as the negative electrode of a sodium ion battery. -1 After 100 cycles at a current density of 1000 mA g -1 After 200 cycles at a current density of , the capacity becomes higher and higher due to activation. The capacity after 200 cycles is higher than the first time, with a capacity retention rate of 104%.

[0025] (6) The raw materials used in the composite material prepared by the present invention are all common commercial and inexpensive materials that can be directly purchased. The preparation process is also relatively simple. In addition, the obtained composite material has excellent electrochemical sodium storage performance and has great application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the infrared spectrum of the precursor prepared in Example 1 of the present invention.

[0027] Figure 2 The X-ray diffraction pattern of the composite material prepared in Example 2 of the present invention.

[0028] Figure 3 The X-ray diffraction pattern of the composite material prepared in Example 2 of the present invention oxidized in air.

[0029] Figure 4 This is the thermogravimetric spectrum of the composite material prepared in Example 2 of the present invention.

[0030] Figure 5 This is a transmission electron microscope image of the composite material prepared in Example 2 of the present invention.

[0031] Figure 6 This is the low-band infrared spectrum of the precursor prepared in Example 3 of the present invention.

[0032] Figure 7 This is the high-band infrared spectrum of the precursor prepared in Example 3 of the present invention.

[0033] Figure 8 This is the thermogravimetric spectrum of the composite material prepared in Example 4 of the present invention.

[0034] Fig. 9 This is a scanning electron microscope image of the composite material prepared in Example 4 of the present invention.

[0035] Fig.10 This is the thermogravimetric spectrum of the composite material prepared in Example 5 of the present invention.

[0036] Fig.11 The composite material prepared in Example 6 of the present invention is used for the negative electrode of a sodium ion battery at 400 mA g -1 Cycling stability at different current densities.

[0037] Fig.12 The composite material prepared in Example 6 of the present invention is used for the negative electrode of a sodium ion battery at 1000 mA g -1 Cycling stability at different current densities.

[0038] Fig.13 The composite material prepared in Example 7 of the present invention is used for the negative electrode of a sodium ion battery at 100 mA g -1 Cycling stability at different current densities.

[0039] Fig.14 This is the thermogravimetric spectrum of the composite material prepared in Example 8 of the present invention.

[0040] Fig.15 The composite material prepared in Example 8 of the present invention is used for the negative electrode of a sodium ion battery at 100 mA g -1 Cycling stability at different current densities.

[0041] Fig.16The composite material prepared in this comparative example 1 is used for the negative electrode of the sodium ion battery at 100mA g -1 Cycling stability at different current densities. DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0043] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0044] Example 1

[0045] Dissolve 2g of glucose in 70ml of deionized water, then transfer into 100ml of Teflon liner and seal in a stainless steel reactor, keep the reaction at 200°C for 6 hours. After the reaction is completed, filter to obtain hydrothermal carbon balls, and dry the hydrothermal carbon balls in a drying oven for later use.

[0046] Dissolve 5.0g SbCl3 in 80ml ethylene glycol to form a transparent solution, then add 0.05g hydrothermal carbon balls, stir, and ultrasonically treat for 30 minutes to form a uniformly dispersed solution. Then transfer the obtained solution to a 100ml Teflon liner and seal it in a stainless steel reactor. Keep it at 180℃ for 24 hours. After the reaction is completed, collect the precursor by centrifugation, wash it with deionized water several times, and dry it in an oven at 60℃ to obtain the precursor. The obtained precursor was tested by infrared spectroscopy, and the results are as follows: Figure 1 shown. Figure 1 It shows that there are many organic polymers on the antimony-containing precursor.

[0047] Example 2

[0048] First, 5.0 g of SbCl3 was dissolved in 80 ml of ethylene glycol to form a transparent solution, and then 0.05 g of hydrothermal carbon balls (the preparation of hydrothermal carbon balls is the same as in Example 1) was added, stirred, and ultrasonically treated for 30 minutes to form a uniformly dispersed solution. The obtained solution was then transferred to a 100 ml Teflon liner and sealed in a stainless steel reactor, and the reaction was maintained at 180°C for 24 hours. After the reaction was completed, the precursor was collected by centrifugation, washed several times with deionized water, and dried in an oven at 60°C to obtain the precursor. Finally, the precursor was treated at 700°C in a 5% H2 / Ar atmosphere for 6 hours to obtain the composite material of the present invention.

[0049] The composite material was characterized by X-ray, and the results were as follows Figure 2 As shown; Figure 2 It shows that the composite material contains antimony.

[0050] The obtained composite material was oxidized at 900°C in air and characterized by X-ray. Figure 3 As shown; Figure 3 It shows that the product of Sb oxidation in the composite material is Sb2O4.

[0051] The obtained composite material was tested by thermogravimetric analysis. Figure 4 As shown; Since the Sb in the composite material is oxidized to Sb2O4 during the thermogravimetric analysis test, according to Figure 4 The test results are given by the formula Among them, M Sb is the molecular weight of antimony (Sb), is the molecular weight of Sb2O4, is the final weight of Sb2O4, m 复合材料 is the initial weight of the composite material, and it can be calculated that the antimony content in the composite material is 47.5wt% and the carbon content is 52.5wt%.

[0052] The composite material was characterized by transmission electron microscopy, and the results are shown in 5; Figure 5 It shows that the antimony in the composite material is uniformly dispersed in the carbon layer, indicating that the carbon coating effect is good.

[0053] Example 3

[0054] First, 5.0 g of SbCl3 was dissolved in 80 ml of ethylene glycol to form a transparent solution, then transferred to a 100 ml Teflon-lined, sealed in a stainless steel reactor, and kept at 180 ° C for 24 hours. After the reaction, the precursor was collected by centrifugation, washed several times with distilled water, and dried in an oven at 60 ° C to obtain the precursor.

[0055] The obtained precursor was tested by infrared spectroscopy, and the results were as follows Figure 6 As shown; and the infrared spectrum test results of the precursor obtained by adding hydrothermal carbon balls in Example 1, the precursor obtained by not adding hydrothermal carbon balls in this example, and the hydrothermal carbon balls are compared, and the results are as follows Figure 7 shown. Figure 6 and 7 It shows that the antimony-containing precursor obtained in this embodiment without adding hydrothermal carbon balls also contains organic polymers, but the signal is lower than the infrared spectrum intensity in Example 1, indicating that the relative content of organic matter in the precursor of this embodiment is small.

[0056] Example 4

[0057] First, 5.0 g of SbCl3 is dissolved in 80 ml of ethylene glycol to form a transparent solution, and then transferred to a 100 ml Teflon liner and sealed in a stainless steel reactor, and kept reacting at 180°C for 24 hours; after the reaction is completed, the precursor is collected by centrifugation, washed several times with deionized water, and dried in an oven at 60°C to obtain the Sb4O5Cl2 precursor mentioned in the composite material of the present invention; finally, the precursor is treated at 700°C for 6 hours in a 5% H2 / Ar atmosphere to obtain the composite material of the present invention.

[0058] The obtained composite material was tested by thermogravimetric analysis. Figure 8 As shown. According to the formula Among them, M Sb is the molecular weight of antimony (Sb), is the molecular weight of Sb2O4, is the final weight of Sb2O4, m 复合材料 is the initial weight of the composite material, and it can be calculated that the antimony content in the composite material is 85wt%, and the carbon content is 15wt%. Comparison of the thermogravimetric analysis results of this embodiment with those of the above-mentioned embodiment 2 shows that by using the method of the present invention, adding hydrothermal carbon balls during the solvent thermal reaction process can increase the carbon content of the precursor after high-temperature reduction.

[0059] The composite material was observed by scanning electron microscopy, and the results are shown in Figure 9; Fig. 9 This shows that the composite particles are somewhat agglomerated.

[0060] Example 5

[0061] First, 5.0 g of SbCl3 was dissolved in 80 ml of ethylene glycol to form a transparent solution, and then 0.05 g of hydrothermal carbon balls (the preparation of hydrothermal carbon balls was the same as in Example 1) was added, stirred, and ultrasonically treated for 30 minutes to form a uniformly dispersed solution. The obtained solution was then transferred to a 100 ml Teflon liner and sealed in a stainless steel reactor, and the reaction was maintained at 180°C for 48 hours. After the reaction was completed, the precursor was collected by centrifugation, washed several times with distilled water, and dried in an oven at 60°C to obtain a Sb4O5Cl2 precursor. Finally, the precursor was treated at 700°C in a 5% H2 / Ar atmosphere for 6 hours to obtain the composite material of the present invention.

[0062] The obtained composite material was tested by thermogravimetric analysis. Fig.10 shown. Fig.10 It shows that according to the formula Among them, M Sb is the molecular weight of antimony (Sb), is the molecular weight of Sb2O4, is the final weight of Sb2O4, m 复合材料is the initial weight of the composite material, and it can be calculated that the antimony content in the composite material is 31.6wt%, and the carbon content is 68.4wt%. Comparison of the thermogravimetric analysis results of this embodiment with those of the above-mentioned embodiment 2 shows that the adjustment of the carbon content in the composite material prepared by the method of the present invention can be achieved by regulating the solvent thermal reaction time.

[0063] Example 6

[0064] According to the mass ratio of 75:10:15, 0.15g of the composite material obtained in the above Example 2, 0.02g of conductive carbon black, and 0.03g of polyacrylic acid were weighed and mixed in a mortar for 30 minutes to obtain a slurry; the obtained slurry was coated on a copper foil, vacuum dried at 100°C for 12 hours, and then cut into electrode sheets with a diameter of about 11mm as working electrodes. Sodium sheets were used as reference electrodes and counter electrodes, Celgard 2400 organic membranes were used as diaphragms, 1M NaPF6 solute was dissolved in a solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, and 5wt% of fluoroethylene carbonate (FEC) was added as an electrolyte. CR2025 button cells were used for electrochemical testing. The results of the electrochemical tests are shown in FIG. Fig.10 and 11 shown. Fig.11 It shows that the prepared electrode has a conductivity of 400 mA g -1 After 100 cycles of current density cycling, the capacity retention rate is 97.2%; Fig.12 It shows that the prepared electrode has a conductivity of 1000 mA g -1 After 200 cycles of current density cycling, the capacity has almost no attenuation, and due to activation, the capacity is getting higher and higher. The capacity after 200 times is even higher than the first time, with a capacity retention rate of 104%.

[0065] Example 7

[0066] According to the mass ratio of 75:10:15, 0.15g of the composite material obtained in the above Example 4, 0.02g of conductive carbon black, and 0.03g of polyacrylic acid were weighed respectively, and then the button cell was assembled according to the preparation method of the electrode in the above Example 6 and the electrochemical performance was tested. The test results are as follows: Fig.13 shown. Fig.13 It shows that the prepared electrode has a -1 After 100 cycles at a current density of 1.54 W, the capacity retention rate was 89.6%.

[0067] Example 8

[0068] First, 5.0g SbCl3 was dissolved in 80ml ethylene glycol to form a transparent solution, and then 0.05g hydrothermal carbon balls (the preparation of hydrothermal carbon balls is the same as in Example 1) were added, stirred, and ultrasonically treated for 30 minutes to form a uniformly dispersed solution. The obtained solution was then transferred to a 100ml Teflon liner and sealed in a stainless steel reactor, and kept reacting at 180°C for 24 hours; after the reaction was completed, the precursor was collected by centrifugation, washed several times with distilled water, and dried in an oven at 60°C to obtain the precursor; finally, the precursor was treated at 600°C in a 5% H2 / Ar atmosphere for 6 hours to obtain the composite material of the present invention.

[0069] The obtained composite material was tested by thermogravimetric analysis. Fig.14 shown. Fig.14 It shows that according to the formula Among them, M Sb is the molecular weight of antimony (Sb), is the molecular weight of Sb2O4, is the final weight of Sb2O4, m 复合材料 is the initial weight of the composite material, and it can be calculated that the antimony content in the composite material is 51.5wt%, and the carbon content is 48.5wt%. Comparison of the thermogravimetric analysis results of this embodiment with those of the above-mentioned embodiment 2 shows that the adjustment of the carbon content in the composite material prepared by the method of the present invention can be achieved by regulating the high-temperature reduction temperature of the precursor.

[0070] The composite material was tested in a button cell and the results are shown in Figure 15. Fig.15 It shows that the prepared electrode has a -1 After 100 cycles at a current density of 1.54 W, the capacity was retained by 86.4%.

[0071] Comparative Example 1

[0072] 80 wt% of antimony and 20 wt% of acetylene black were weighed, and a solid-state carbon-coated antimony composite material was obtained by high-energy ball milling at 400 r / min. Then, 0.15 g of the composite material, 0.02 g of conductive carbon black, and 0.03 g of polyacrylic acid were weighed according to a mass ratio of 75:10:15. Then, according to the preparation method of the electrode in Example 6 above, a button cell was assembled and the electrochemical performance was tested. The test results are as follows: Fig.16 shown. Fig.16 It shows that the prepared electrode has a -1 After 100 cycles at a current density of 1.50 Å, the capacity retention rate was only 63.7%, indicating that the cycle performance of the carbon-coated antimony prepared by the solid-state method is obviously inferior to that of the carbon-coated antimony composite material prepared by the present invention.

[0073] The composite negative electrode material of metal antimony and carbon applicable to the present invention is not limited to the specific application in the field of sodium ion batteries in the above embodiments, and can also be used in lithium ion batteries and potassium ion batteries.

[0074] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a metal antimony and carbon composite material, characterized in that: Antimony trichloride is dissolved in ethylene glycol, and then hydrothermal carbon balls are added, stirred evenly, and then transferred to a reactor for solvent thermal reaction, heated to a set temperature and insulation time to obtain a precursor, and finally the precursor is reduced to a composite material of metal antimony and carbon in a high-temperature reducing atmosphere.

2. The method for preparing the metal antimony and carbon composite material according to claim 1, characterized in that: The mass fraction of carbon in the prepared composite material of metal antimony and carbon ranges from 15.2wt% to 68.4wt%.

3. The method for preparing the metal antimony and carbon composite material according to claim 1, characterized in that: The mass ratio of the hydrothermal carbon balls to antimony trichloride is 1:100, and the amount of ethylene glycol added is 70-80% of the volume of the reactor.

4. The method for preparing the metal antimony and carbon composite material according to claim 1, characterized in that: The hydrothermal carbon spheres are prepared by a glucose hydrothermal method.

5. The method for preparing the metal antimony and carbon composite material according to claim 1, characterized in that: The temperature of the solvent thermal reaction is 180-200°C.

6. The method for preparing the metal antimony and carbon composite material according to claim 1, characterized in that: The solvent thermal reaction time is 24-48h.

7. The method for preparing the metal antimony and carbon composite material according to claim 1, characterized in that: The high temperature reduction temperature of the precursor is 500-700°C.

8. A composite material of metal antimony and carbon, characterized in that: The method is prepared by any one of claims 1 to 7.

9. Use of the composite material of metal antimony and carbon as claimed in claim 8 as a negative electrode material in an alkali metal ion battery.

Citation Information

Patent Citations

  • Core-shell type carbon microspheres and preparation method and application thereof

    CN103102509A

  • Carbon-coated nano-antimony composite material as well as preparation method and application thereof

    CN104201359A

  • Antimony-carbon composite material and preparation method and application thereof

    CN106887572A

  • Preparation method of hollow oxide microspheres

    CN107140606A

  • Antimony nitrogen carbon nanosheet as well as preparation method and application thereof

    CN116534811A